2006
DOI: 10.1021/ma052590x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Near-Field and Confocal Raman Microscopic Investigation of P3HT−PCBM Systems for Solar Cell Applications

Abstract: The morphological evolution of thin composite films based on poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl C 61 butyric acid methyl ester (PCBM) upon annealing has been studied by means of transmission electron microscopy (TEM), scanning near-field optical microscopy (SNOM), and confocal Raman microscopy. This system currently is the most promising candidate for high-performance polymer solar cells. TEM bright field and SNOM topography measurements show that segregation and large-scale crystallization of PCBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
116
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 32 publications
11
116
0
1
Order By: Relevance
“…Superior path balance for case 1 can be one of the reasons for the reported improved performance via a postannealing protocol. [1][2][3][4][5][6][7]10 iii. Intra-and Intermolecular Transport along Hole Pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Superior path balance for case 1 can be one of the reasons for the reported improved performance via a postannealing protocol. [1][2][3][4][5][6][7]10 iii. Intra-and Intermolecular Transport along Hole Pathways.…”
Section: Resultsmentioning
confidence: 99%
“…In blend materials however, when annealed, the segregated PCBM small molecules diffuse into the P3HT matrix allowing the latter to re-organize itself into stacks and long chains as a result of the increase in mean free volume. Raman microscopy results have previously shown that upon annealing the relative position of P3HT remains largely the same while that of PCBM changes, a clear indication that PCBM aggregates and diffuses into P3HT matrix during the annealing process (Klimov et al, 2006;Marchaut and Foot, 1997;Hugger et al, 2003;Zhao et al, 2009). This study indicates that crystallization of P3HT in the blends upon annealing improves the absorption of the films and causes a red shift to occur in the spectra of the blends.…”
Section: The Characteristic High Resolution Transmission Electron Micmentioning
confidence: 98%
“…1,[9][10][11] It is less clear, however, how annealing affects the fullerene component of a BHJ polymer solar cell: the way in which the fullerene molecules are distributed in the polymer matrix and the details of the BHJ morphology have been the subject of much debate. 1,2,9,10,[12][13][14][15] In this work, we directly address the question of what happens to the fullerene component of a polymer BHJ solar cell upon thermal annealing. By fabricating "fullerene-only" BHJ halfdevices (that use electronically insulating polystyrene (PS) rather than a semiconducting polymer like P3HT), we show that thermal annealing causes a decrease in the ability of the fullerene network to conduct electrons as a result of increased phase segregation of the blended polymer and fullerene components.…”
Section: Introductionmentioning
confidence: 99%